1989
DOI: 10.1017/s1323358000023262
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Transient Events at 843 MHz

Abstract: The Molonglo Observatory Synthesis Telescope is equipped with a transient event monitoring system which operates during normal synthesis observations. The device is designed to respond to impulsive signals which occur within the passband (843.0 ± 1.5 MHz) with time scales between 0.001 ms and 800 ms. The multiple beam facility of the telescope provides some discrimination against local interference. An upper limit of 1.7 × 10−2 events s−1 sr−1 has been placed on celestial events with durations between 1 ms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
(7 reference statements)
0
28
0
Order By: Relevance
“…Other special modes are used for tasks such as the calibration of beam gains. • A transient event recorder (Amy et al 1989) looks for impulsive events in whatever field the telescope is observing.…”
Section: (E) Specifications Of the Mostmentioning
confidence: 99%
“…Other special modes are used for tasks such as the calibration of beam gains. • A transient event recorder (Amy et al 1989) looks for impulsive events in whatever field the telescope is observing.…”
Section: (E) Specifications Of the Mostmentioning
confidence: 99%
“…Cortiglioni et al (1981), Inzani et al (1982), and Amy et al (1989) all detected some dispersed radio pulses, but found no convincing associations with GRBs. Balsano (1999) found a dispersed radio pulse apparently coincident with GRB 980329, but it was narrowband, which has led to it being interpreted as due to terrestrial interference.…”
Section: Gamma-ray Bursts (Grbs)mentioning
confidence: 86%
“…Our focus is on comparison with MOTOR (Amy et al 1989) and STARE (Katz et al 2003), as both represent nearly all-sky surveys at frequencies below 1 GHz.…”
Section: Astronomical Radio Transientsmentioning
confidence: 99%
“…Radio Supernovae: Colgate & Noerdlinger (1971) predicted that a supernova explosion should produce a large, broadband radio pulse (< 1 s), though no such pulses have yet been detected (Huguenin & Moore 1974, Kardashev et al 1977). γ-ray Bursts: Cortiglioni et al (1981), Inzani et al (1982), and Amy et al (1989) detected dispersed radio pulses but found no convincing associations with gamma-ray burst sources. Various searches for radio pulses associated with gamma-ray bursts (including precursor pulses) have been conducted (Koranyi et al 1995;.…”
Section: Radio Transientsmentioning
confidence: 94%